THE ANALYSIS OF CODE SWITCHING AND MIXED CODE OF LANGUAGE STUDENTS OF PBSID STKIP GETSEMPENA IN BANDA ACEH LECTURES DISCUSSION FORUM - Wahidah Nasution; Khairunnissah (Jurnal Metamorfosa, 2015)
This study was conducted because of the transition and mixed language that occurs in a formal situation in the lecturers discussion forum. The focus of this study is the use of code switching and code-mixing of the students of PBSID academic year 2013 at STKIP Bina Bangsa Getsempena Banda Aceh in the course of discussion forum. This study aimed to describe the nature and occurrence factor code switching and code-mixing of students PBSID. This research uses a qualitative research approach. The data obtained in this study was from students’ speech that occurs in the course of discussion forum. Data collection techniques in this study were interviews, recording and notes. Data analysis techniques in this study were interactive techniques. Based on the survey, it was found the phenomenon of students’ code switching. A form of code that appears were in the form of an internal code switching. A form of mixed code that appears was in the form of (1) a form of words, (2) a form of phrase and form baster. The factors of code caused by (1) the presence of a third factor, (2) the factors likely to arouse a sense of humor, and (3) factors speakers.